2017
DOI: 10.2147/ceg.s142644
|View full text |Cite
|
Sign up to set email alerts
|

Risks of PEG tube placement in patients with cirrhosis-associated ascites

Abstract: This study examined the safety of placing percutaneous endoscopic gastrostomy (PEG) tube in people with liver cirrhosis. The target population was further subdivided into people with ascites (case group) and people without ascites (control). We compare the morbidity and the mortality difference of PEG placement in cirrhotic patients with ascites vs cirrhotic patients without ascites. We then examined multiple factors including sex, race, chronic illness including hypertension, congestive heart failure, and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A retrospective study of 29 patients with advanced cirrhosis undergoing PEG insertion [63] showed that the presence of ascites may be associated with increased mortality risk. However, a more recent study of 583 patients with cirrhosis (107 with ascites [18.3 %]), did not show any significant difference for bleeding, infection, or mortality in patients with ascites [64]. PEG tubes may be placed successfully after paracentesis, if re-accumulation can be prevented for a period of 7 -10 days after tube insertion, in order to allow tract maturation.…”
Section: Contraindications To Ngt/njt Insertionmentioning
confidence: 99%
“…A retrospective study of 29 patients with advanced cirrhosis undergoing PEG insertion [63] showed that the presence of ascites may be associated with increased mortality risk. However, a more recent study of 583 patients with cirrhosis (107 with ascites [18.3 %]), did not show any significant difference for bleeding, infection, or mortality in patients with ascites [64]. PEG tubes may be placed successfully after paracentesis, if re-accumulation can be prevented for a period of 7 -10 days after tube insertion, in order to allow tract maturation.…”
Section: Contraindications To Ngt/njt Insertionmentioning
confidence: 99%
“…In patients who are unable to consume adequate nutrition orally for appropriate growth, nasogastric (or nasojejunal) feeding is required. The insertion of a percutaneous gastrostomy carries significant risk in patients with portal hypertension and should be avoided (99,100). Failure to achieve adequate nutrition and growth using enteral feeds should prompt use of PN (82,83,85).…”
Section: Approach To Nutritional Support Of Children With Cirrhosismentioning
confidence: 99%
“…These results are in concordance with conventional practices, where ascites is considered a contraindication to PEG placement in most cases. Another study using the NIS showed that, although associated with a higher rate of complications, the presence of ascites among cirrhotic patients was associated with lower all-cause mortality as compared to cirrhotic patients without ascites [ 25 ]. Unlike this study, where only patients with cirrhosis-associated ascites were taken into consideration, our study analyzed the outcomes of PEG among all patients with ascites, irrespective of the underlying cause, over a much longer time period.…”
Section: Discussionmentioning
confidence: 99%